Tanino condensado de acácia-negra (Acacia mearnsii) na dieta de leitões de creche - Schneider, Luciane Inês (2022)
Phytogenic additives are examples of potential alternatives to decrease the digestive upsets in the first weeks after weaning piglets. Tannin is a polyphenolic compound which form complex molecules and may be a solution for weaning piglets diarrhea and gut health negative effects. This study aimed to evaluate the effects of Black-wattle condensed tannin extract inclusion in simple and complex diets on performance, fecal consistency score and serum haptoglobin level in weaned piglets. A total of 88 commercial breed weaning piglets, with initial body weight of 8.02 ± 1.21 kilograms (kg), were housed in a masonry facility and pens equipped with a feeder and a biteball drinker. The experimental period was 28 days, and the feeding program consisted of three diets (pre-starter I, pre-starter II and starter), with nutritional levels adjusted according to the phase. The animals were distributed in four treatments in a 2² factorial experiment: simple diet (DS), simple diet + tannin (DS+T), complex diet (DC) and complex diet + tannin (DC+T), with 11 replications and two piglets per pen. The design was a randomized block design according to the initial body weight. The animals were weekly weighed, and feed intake and leftovers were measuring. The faecal consistency score was determined twice a day, by two trained evaluators, by three weeks after weaning. Blood samples for serum haptoglobin concentration were collected at 7 and 14 days of the experiment. The addition of condensed tannin had no effect (P>0.05) on weaned piglets performance variables. The complexity of the diet also did not result in differences (P>0.05) in piglet performance. However, piglets fed DC+T diet had a lower incidence of liquid faeces in experimental period. And the piglets fed DS+T diet had a lower blood haptoglobin concentration level.